Strategic Marketing for Restaurant Business (Case Study of Lawangwangi Café) - Gurhananda, Ivan; Wandebori, Harimukti (Journal of Business and Management, 2014)
Abstract- The purpose of this research is to examine the restaurant strategy by discussing the relationship between the current condition and the service quality of Lawangwangi Café. The research objective is to determine a current condition of the Lawangwangi Café, develop new strategy for the company, and give recommendation for better performance of the company. This research presented the theories that come from the experts. It used to identify and analyse the data and also as the support to answers the research question. The theory used in this research are Service Quailty, External and Internal Analysis, SWOT Analysis, Corporate Strategy, Business Strategy, and Functional Strategy.  For the methods and gathered data, this research used problem identification, exploratory research, external and internal analysis, analysis of strategic factors, strategy formulation, then conclusion and recommendation. For exploratory research, this research used a questionnaire that spreaded to 100 respondents, the respondents were Lawangwangi Café customers. An interview with the owner of the Lawangwangi Café also conducted in this research. After the data gathered from the questionnaire and interview, this research analyzed the data. First is the questionnaire data, it is divided into 5 sections analysis, which are demography, gap between customer expectation toward service given of Lawangwangi Café, Lawangwangi Café’s food and beverage quality, customer behavior, and their recommendation for Lawangwangi Café. The next analysis conduct of interview result, This part explored the information about the management and development of Lawangwangi Café. After that, this research analysed to determine new strategy to be implemented in the Lawangwangi Café in order to improve the service performance to gain more customer. The last part is to determine the conclusion and provide a recommendation in the form of strategy for Lawangwangi Café. The recommended strategies were to do a proper employee training, service quality controlling, hired a professional restaurant manager, and enhance the promotion like student promotion, by showing their student card they can get a discount on weekdays, every Tuesday by showing a student card, they get free ice tea for minimum order Rp. 35.000. Those of promos would become a new attraction for Lawangwangi Café to attract more customers Keyword: restaurant strategy, service quality, external and internal analysis, SWOT analysis